Screening of Children’s Nutrition Status in New Normal Era - Syariefah Hidayati Waliulu; Sahrir Sillehu; Rahma Tunny (Humanistic Network for Science and Technology (HNST), 2022)
Nutritional status is an important aspect of children's health, especially at the infant age. Optimal growth allows the infant to do activities well and can improve child development. In the new normal era, parents are still worried about bringing their children to health facilities to control the children's nutritional status and other health statuses. This study aims to monitor the nutritional status of children in the new normal era. The screening had been carried out on babies aged 6-12 months involving 90 babies by total sampling in the working area of Pelauw Health Center, Pulau Haruku District, Indonesia. The research design employed in this study was descriptive quantitative to describe the nutritional status of children. The results obtained showed that 71% of infants had normal nutrition category, while the rest had less and very less nutritional status, as well as the risk of overweight. The results indicate that health workers and health academics should conduct door-to-door screening to monitor children’s nutritional status during the Covid-19 outbreak and educate parents in increasing balanced nutritional intake in the new normal era. Keywords: nutritional status; children; new normal era